(3GdETQGa Ydi fSH GdCbWGH GdCQHYI GdCTQGas - (3YHO GdSdGe Hf GdWjH Hf eMeO GdbGOQj GdMSfj GdeZQHj GdaGSj, CHh eMeO,J (B1110 (3g` s
(3ChdgG (B:s
(3MeOkG def bO CUWai Bd GdfHi aj TQa hfSH hMSH s
(3BNQgG (B:s
(3hBdg hUMHg GdCNjGQ hef JdGge bGHSi GdCfhGQ hgj ai PcQ GdeTGjN(B: (3YHOGdbGOQ GdLjdGfi, YHOGdSdGe Hf eTjT, CHhGdMSf GdTGPdi, eMeO Hf SdjeGf GdLQhdj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B24 - (3U(B34s
(3hgj aj PcQ GdeTGjN (B: (3YHOGdbGOQ GdLjdGfj, YHOGdSdGe Hf eTjT, CHhGdMSf GdTGPdj, eMeO Hf SdjeGf GdLRhdj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B682 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B310) s
Keywords: (3GdJGQjNs